A High Responsivity and Photosensitivity Self‐Powered UV Photodetector Constructed by the CuZnS/Ga2O3 Heterojunction. Issue 5 (4th December 2022) - Lv, Zunxian; Yan, Shiqi; Mu, Wenxiang; Liu, Yiyuan; Xin, Qian; Liu, Yang; Jia, Zhitai; Tao, Xutang
Abstract: Fabricating a heterojunction photodetector is efficient to take advantage of the built‐in electric field formed by heterojunction and thus improve the performance of photodetector. Herein, a CuZnS/Ga2 O3 type‐II heterojunction photodetector is designed and constructed by chemical bath deposition for the first time. The photodetector exhibits super high rectifying characteristics (5.7 × 10 4 at ± 1 V), high responsivity (48.01 mA W −1 at 0 V), and detectivity (1.83 × 10 12  Jones at 0 V), which are higher than most of the reported inorganic devices as far as the authors know. Benefiting from built‐in electric field constructed by the CuZnS/Ga2 O3 type‐II heterojunction, the photo‐induced electron and hole pairs are quickly separated by the built‐in electric field between the Ga2 O3 and the CuZnS interface. Therefore, the photodetector constructed by CuZnS/Ga2 O3 type‐II heterojunction shows a prominent self‐powered performance. At zero bias, the photodetector shows a fast photoresponse (rise time τr  = 70 ms, decay time τd  = 10 ms). These data of performance are significantly excellent to most of the reported Ga2 O3 heterojunction photodetectors. These performances strongly suggest that the CuZnS/Ga2 O3 photodetector has great potential in ultra‐high performance self‐powered solar‐blind photodetector. Abstract : A CuZnS/Ga2 O3 type‐II heterojunction photodetector is constructed by sequential chemical bath deposition. Benefiting from built‐in electric field constructed by the CuZnS/Ga2 O3 type‐II heterojunction, the photodetector exhibits super high rectifying characteristics (5.7 × 10 4 at ±1 V), high responsivity (48.01 mA W −1 at 0 V), and detectivity (1.83 × 10 12  Jones at 0 V).